The effect of molecular weight and hydrolysis degree of poly(vinyl alcohol)(PVA) on the thermal and mechanical properties of poly(lactic acid)/PVA blends - Iván Restrepo; Carlos Medina; Viviana Meruane; Ali Akbari-Fakhrabadi; Paulo Flores; Saddys Rodríguez-Llamazares (Polímeros, 2018)
Abstract The effect of molecular weights and hydrolysis degrees (HD) of polyvinyl alcohol (PVA) on thermal and mechanical properties and crystallinity of polylactic acid (PLA)/PVA blends was investigated. Blends were prepared by the melt blending method using PLA/PVA ratios: 80/20, 90/10 and 97/3 wt. %. A single glass transition temperatures was observed for all PLA/PVA blends, suggesting the formation of binary compatible blends at concentration range studied. Thermogravimetric analysis results showed a better thermal stability for PLA/PVA blends containing PVA of higher Mw and HD. According to mechanical properties, low quantities of PVA (3 wt. %) do not affect the tensile strength of blends (irrespective of Mw and HD). However, as the PVA content increases, tensile strength tends to lower values, especially for blends with 20 wt.% of PVA, with 98% of HD.